Patient-Specific Computer Simulation to Elucidate the Role of Contact Pressure in the Development of New Conduction Abnormalities After Catheter-Based Implantation of a Self-Expanding Aortic Valve. (February 2018) - Rocatello, Giorgia; El Faquir, Nahid; De Santis, Gianluca; Iannaccone, Francesco; Bosmans, Johan; De Backer, Ole; Sondergaard, Lars; Segers, Patrick; De Beule, Matthieu; de Jaegere, Peter; Mortier, Peter
Abstract : Background—: The extent to which pressure generated by the valve on the aortic root plays a role in the genesis of conduction abnormalities after transcatheter aortic valve replacement (TAVR) is unknown. This study elucidates the role of contact pressure and contact pressure area in the development of conduction abnormalities after TAVR using patient-specific computer simulations. Methods and Results—: Finite-element computer simulations were performed to simulate TAVR of 112 patients who had undergone TAVR with the self-expanding CoreValve/Evolut R valve. On the basis of preoperative multi-slice computed tomography, a patient-specific region of the aortic root containing the atrioventricular conduction system was determined by identifying the membranous septum. Contact pressure and contact pressure index (percentage of area subjected to pressure) were quantified and compared in patients with and without new conduction abnormalities. Sixty-two patients (55%) developed a new left bundle branch block or a high-degree atrioventricular block after TAVR. Maximum contact pressure and contact pressure index (median [interquartile range]) were significantly higher in patients with compared with those without new conduction abnormalities (0.51 MPa [0.43–0.70 MPa] and 33% [22%–44%], respectively, versus 0.29 MPa [0.06–0.50 MPa] and 12% [1%–28%]). By multivariable regression analysis, only maximum contact pressure (odds ratio, 1.35; confidence interval, 1.1–1.7; P =0.01) and contact pressure index (odds ratio, 1.52; confidence interval, 1.1–2.1; P =0.01) were identified as independent predictors for conduction abnormalities, but not implantation depth. Conclusions—: Patient-specific computer simulations revealed that maximum contact pressure and contact pressure index are both associated with new conduction abnormalities after CoreValve/Evolut R implantation and can predict which patient will have conduction abnormalities. Abstract : Supplemental Digital Content is available in the text.